Translation Strategies of Idioms: With Special Reference to “Anak Semua Bangsa” and “Child of All Nations” - Ngurah Dwi Suryawan, Gusti Agung; Winaya, I Made (Humanis; Vol 22 No 3 (2018), 2018)
This research entitled “Translation Strategies of Idioms: With Special Reference to “Anak Semua Bangsa” and “Child of All Nations”. The aims of this research are to find out the translation strategies applied by the translator in translating the idioms of ST to the TT and to identify the types of equivalence of the translated idioms. The data were in form of idioms collected from an Indonesian novel “Anak Semua Bangsa” and its English translation “Child of All Nations” . Observation method and note-taking technique was used in collecting the data . The data were analyzed using descriptive-qualitative method . In order to answer the formulated questions, the theory of translation strategies of translating idiom proposed by Mona Baker in “In Other Words” (1992) was applied in analyzing the translation strategies used by the translator in translating the idioms in the novels and the theory of equivalence proposed by Eugene Nida in Toward a Science of Translating (1964) to identify the types of equivalence of the translated idioms. The results indicate that there are only three translation strategies found in the translation of 20 idioms used as the data in this study. Moreover, both Nida’s theory of Formal and Dynamic Equivalence were found in the translation of the idioms.